2020
DOI: 10.1101/2020.10.23.20218073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of filtration efficacy of various types of facemasks using ambient and PAO aerosols following with different sterilization methods

Abstract: Due to the ongoing pandemic, various types of facemasks such as N-95, surgical mask and cloth masks are being used as an essential protective measure. The filtration efficiency of these masks were tested before and after sterilization by different methods for two flow rates conditions corresponding to normal breathe rate (20 lpm) and during sneezing (90 lpm). Sterilization techniques used here are autoclaving (30 and 60 minutes), dry oven heating (30 and 60 minutes), gamma irradiation (15 and 25 kGy), hot wate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Also, our data observed that cloth mask (FE=23.2-75.4%) and unsealed surgical mask (FE=37.4-66.4%) offered comparable FE at particle sizes between 0.3 and 5 µm. In agreement with our findings, a recent report showed almost equal FE of cloth masks (FE=19.5-81.8%) and unsealed surgical masks (FE=20.8-77.3%) at particle sizes between 0.3 and 5 µm (Kumar et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Also, our data observed that cloth mask (FE=23.2-75.4%) and unsealed surgical mask (FE=37.4-66.4%) offered comparable FE at particle sizes between 0.3 and 5 µm. In agreement with our findings, a recent report showed almost equal FE of cloth masks (FE=19.5-81.8%) and unsealed surgical masks (FE=20.8-77.3%) at particle sizes between 0.3 and 5 µm (Kumar et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Another study also observed a stable FE (only 0.4% reduction in FE) of 3M-1860 N95 following a single STERIS-VHP cycle using the NIOSH assessment method to evaluate FE [ 46 ]. Furthermore, four reports confirmed the latter studies and showed that 3 to 10 VHP cycles did not affect the FE stability of different types of 3M-N95 masks [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 65%
“…Several non-traditional sterilization/decontamination methods have evaluated with various successes (Hearn et al, 2020 and Kumar et al, 2020 c). Many potential sterilization methods have been explored already, and they are based on chemical and physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The dry/ steam heat treatment has emerged as a promising and straightforward reprocessing method of respirators with good scalability and uniformity disinfection (Xiang et al, 2020; Liao et al, 2020). The steam sterilization by autoclave found helpful as far as filtration efficiency, but it has slightly melted the N95 mask plastic cord (Kumar et al, 2020 c). However, understanding the physical and chemical changes induced by the above various treatments remains unexplored or incomplete in a few cases.…”
Section: Introductionmentioning
confidence: 99%